2007
DOI: 10.1186/1471-2458-7-71
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards prisoners, as reported by prison inmates, prison employees and college students

Abstract: Background: Positive attitudes towards prisoners are important in securing the effectiveness of various correctional rehabilitation programs and the successful reintegration of prisoners after release. We wanted to investigate the attitudes towards prisoners among prison inmates, prison employees and college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
73
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 18 publications
7
73
0
4
Order By: Relevance
“…The existing research on attitudes toward prisoners has focused mainly on gender and on differences in attitudes between professions, in particular rehabilitation teams, law enforcement officers, correction officers, and the public (Horn and Hollin 1997;Kjelsberg et al 2007;Melvin et al 1985;Murphy and Brown 2000;Na and Lofius 1998;Ortet-Fabregat et al 1993). Research has shown that police officers (Horn and Hollin 1997) and correction officers (Kjelsberg et al 2007;Ortet-Fabregat et al 1993) have the least favorable attitudes toward prisoners, whereas, as would be expected, those whose work relates to rehabilitation exhibit the most positive attitudes toward prisoners (Melvin et al 1985;Ortet-Fabregat et al 1993). Given the substantial role of prison volunteers within correctional institutions, it is somewhat surprising that their attitudes toward prisoners have never been measured.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing research on attitudes toward prisoners has focused mainly on gender and on differences in attitudes between professions, in particular rehabilitation teams, law enforcement officers, correction officers, and the public (Horn and Hollin 1997;Kjelsberg et al 2007;Melvin et al 1985;Murphy and Brown 2000;Na and Lofius 1998;Ortet-Fabregat et al 1993). Research has shown that police officers (Horn and Hollin 1997) and correction officers (Kjelsberg et al 2007;Ortet-Fabregat et al 1993) have the least favorable attitudes toward prisoners, whereas, as would be expected, those whose work relates to rehabilitation exhibit the most positive attitudes toward prisoners (Melvin et al 1985;Ortet-Fabregat et al 1993). Given the substantial role of prison volunteers within correctional institutions, it is somewhat surprising that their attitudes toward prisoners have never been measured.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although this is a new construct, previous research on public attitudes regarding prisoners and ex-prisoners (Demski and McGlynn 1999;Helfgott 1997;Homant and Kennedy 1982;Hurwitz and Peffley 1997;Kjelsberg et al 2007;Steffensmeier and Kramer 1980) and on support for rehabilitation (Applegate et al 1997(Applegate et al , 2000Cullen et al 1983Cullen et al , 1990McCorkle 1993) suggests that members of the public likely have very divergent views on this key dimension. The relationship between belief in redeemability and punitiveness, controlling for internality/externality of attributions, is explored in our analysis below.…”
mentioning
confidence: 91%
“…Plotted for each video separately (Figure 3b), no systematic effects of advance information on eye movements is found. Moreover, a mixed effects analysis (with random Kjelsberg et al, 2007).…”
Section: Participantsmentioning
confidence: 99%
“…The study of attitudes often relies on questionnaires (e.g., the attitudes towards prisoners scale, Kjelsberg, Skoglund, & Rustad, 2007;Melvin, Gramling, & Gardner, 1985), which can suffer from a social desirability bias (Hebert, Clemow, Pbert, Ockene, & Ockene, 1995;Mortel et al, 2008;Nederhof, 1985). Alternatively, reaction time measures are used, such as in the implicit association test (IAT, Greenwald, McGhee, & Schwartz, 1998), but these have been criticized for measuring associations rather than attitudes (Fiedler, Messner, & Bluemke, 2006;De Houwer, 2002), and often depend on the ability to read words quickly.…”
mentioning
confidence: 99%